The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1158/1055-9965.epi-19-0799
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer in San Francisco: Disentangling Disparities at the Neighborhood Level

Abstract: Background: This study uses a novel geographic approach to summarize the distribution of breast cancer in San Francisco and aims to identify the neighborhoods and racial/ethnic groups that are disproportionately affected by this disease.Methods: Nine geographic groupings were newly defined based on racial/ethnic composition and neighborhood socioeconomic status. Distribution of breast cancer cases from the Greater Bay Area Cancer Registry in these zones were examined. Multivariable logistic regression models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…TNBC, one of the most aggressive forms of breast cancer, has limited treatment options that are ineffective when the cancer is diagnosed at later stages [25][26][27][28][29]. Since AA women tend to be diagnosed at later stages [30,31], at an early age [32][33][34], and suffer higher rates of TNBC, these factors likely contribute to AAs having the highest breast cancer mortality rate among all race groups.…”
Section: Introductionmentioning
confidence: 99%
“…TNBC, one of the most aggressive forms of breast cancer, has limited treatment options that are ineffective when the cancer is diagnosed at later stages [25][26][27][28][29]. Since AA women tend to be diagnosed at later stages [30,31], at an early age [32][33][34], and suffer higher rates of TNBC, these factors likely contribute to AAs having the highest breast cancer mortality rate among all race groups.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the majority of studies did not consider the geographic distribution of the disease to account for the possibility that nearby neighborhoods are more likely to be similar to one another. Recent geospatial cluster analyses show some nSES measures may be more effective than others at explaining the geospatial distribution of cancer within a particular state, 10 and that differences in nSES by neighborhood or geographic location, including living in an urban versus rural area, 101 could affect cancer mortality 102 . This suggests additional studies that consider spatial associations, urbanicity, and evaluate more than one existing nSES index are warranted before particular nSES measures can be recommended as a standard (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, the majority of studies reviewed were conducted in California, a national leader in the evaluation of nSES and cancer outcomes which can serve as a model for other states 126 . However, in order to move towards standardized nSES index measures, studies across more US states are needed, given that the variation in nSES indices and their associated variables likely differ by geography 102 . Fifth, the majority of reviewed studies utilized State Cancer Registries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That system has been developed by a team led by Scarlett Lin Gomez, PhD, MPH, a professor of epidemiology and biostatistics at the University of California at San Francisco. One of her recent studies found that patients living in San Francisco neighborhoods with a lower socioeconomic status and larger minority populations had worse outcomes for breast cancer . The study revealed both neighborhood‐level and racial/ethnic differences in the stage of diagnosis, the molecular subtype of the tumor, survival, and mortality.…”
Section: Multilayer Impacts On Cancer Outcomesmentioning
confidence: 97%